Implementing efficient market structure - Veronika Grimm; Frank Riedel; Elmar Wolfstetter (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
This article studies the design of optimal mechanisms to regulate entry in natural oligopoly markets, assuming the regulator is unable to control the behavior of firms once they are in the market. We adapt the Clarke-Groves mechanism, characterize the optimal mechanism that maximizes the weighted sum of expected social surplus and expected tax revenue, and show that these mechanisms generally avoid budget deficits and prevent excessive entry.
urn:nbn:de:kobv:11-10047235
Keywords: D43; D44; D45; H20; L13; 330; auctions; mechanism design; natural oligopoly; entry